7th month - Toh, Adelene Seow Kit (2015)
My 2D animation explores a horror theme in a modern society where tradition is becoming less apparent and the meaningful point of the film is to highlight its importance to the audience. In this report, I broke down the production process and the thoughts behind making the film.